AGLOMERASI ETNIS MADURA DI KAMPUNG GADANG KELURAHAN KAMPUNG GADANG KECAMATAN BENJARMASIN TENGAH BERDASARKAN SISTEM EKONOMI - Andri Susana Lestari (JURNAL SOCIUS, 2013)
This thesis talk about How and Why the Madurese ethnic agglomeration based on the type of occupation(work). This research will give some benefits in theoretically and practically. This research will make some additions for working anthropology theoretical. Practically, especially (1) to the researcher and observer, this research is able to give scientific information which able is used as an orientation for doing next study that will give depth explore in Madurese ethnic agglomeration based on the type of occupation (work) , (2) to give an implication in learning social subject especially about ethnic agglomeration,(3) to policy maker, this research is able to give some inputs about the policies which is giving more attention in ethnic agglomeration, that will influence the interaction between groups and pluralistic society.Key words: Aglomeration, Ethnic, and Work